Evaluation of Crisis Handling of Carasun Cosmetic Company - Reksananda Shindy Priskila; Dwi Prasetyo (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Threats to a company's existence can arise from a reputation crisis induced by various factors. If not handled carefully, such a reputation crisis can lead to a loss of trust from customers, investors, and employees, which, in turn, can have a detrimental impact on the overall company's performance. For example, Carasun, a cosmetics company, faced a reputation crisis due to allegations of using "buzzers" to tarnish the reputation of its competitor, Skingame. The research on Carasun's crisis aims to identify the triggering factors of the reputation crisis, evaluate the negative impacts experienced by Carasun, and analyze the company's crisis management efforts. This research uses a qualitative research method with a case study approach, and the findings indicate that Carasun's reputation crisis was triggered by the improper use of "buzzers" and negative posts on social media. The impacts of this crisis included a decrease in consumer trust, disruptions in business partner relationships, and threats to the company's sustainability. To address this crisis, Carasun has implemented crisis management strategies, including adaptive strategies and utilizing social media as a crisis communication tool. Recommendations for cosmetics companies facing reputation crises involving "buzzers" include increasing awareness of early crisis signs, improving the ability to identify crisis signs through technology and data analysis, and strengthening internal coordination and communication by prioritizing ethical values and integrity.